Pediatric stroke and transcranial direct current stimulation: methods for rational individualized dose optimization - Gillick, Bernadette T.; Kirton, Adam; Carmel, Jason B.; Minhas, Preet; Bikson, Marom (Frontiers in Human Neuroscience, 2014)
Background- Transcranial direct current stimulation (tDCS) has been investigated mainly in adults and doses may not be appropriate in pediatric applications. In perinatal stroke where potential applications are promising, rational adaptation of dosage for children remains under investigation. Objective - Construct child-specific tDCS dosing parameters through case study within a perinatal stroke tDCS safety and feasibility trial. Methods- 10-year-old subject with a diagnosis of presumed perinatal ischemic stroke and hemiparesis was identified. T1 MRI scans used to derive computerized model for current flow and electrode positions. Workflow using modeling results and consideration of dosage in previous clinical trials was incorporated. Prior Ad hoc adult montages versus de novo optimized montages provided distinct risk benefit analysis. Approximating adult dose required consideration of changes in both peak brain current flow and distribution which further tradeoff between maximizing efficacy and adding safety factors. Electrode size, position, current intensity, compliance voltage, and duration were controlled independently in this process. Results- Brain electric fields modeled and compared to values previously predicted models. Approximating conservative brain current flow patterns and intensities used in previous adult trials for comparable indications, the optimal current intensity established was 0.7 mA for 10 minutes with a tDCS C3/C4 montage. Specifically 0.7 mA produced comparable peak brain current intensity of an average adult receiving 1.0 mA. Electrode size of 5x7 cm2 with 1.0 mA and low-voltage tDCS was employed to maximize tolerability. Safety and feasibility confirmed with subject tolerating the session well and no serious adverse events. Conclusion- Rational approaches to dose customization, with steps informed by computational modeling, may improve guidance for pediatric stroke tDCS trials.